2006
DOI: 10.1038/ni1305
|View full text |Cite
|
Sign up to set email alerts
|

The Birc1e cytosolic pattern-recognition receptor contributes to the detection and control of Legionella pneumophila infection

Abstract: Baculovirus inhibitor of apoptosis repeat-containing 1 (Birc1) proteins have homology to several germline-encoded receptors of the innate immune system. However, their function in immune surveillance is not clear. Here we describe a Birc1e-dependent signaling pathway that restricted replication of the intracellular pathogen Legionella pneumophila in mouse macrophages. Translocation of bacterial products into host-cell cytosol was essential for Birc1e-mediated control of bacterial replication. Caspase-1 was req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
584
0
34

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(637 citation statements)
references
References 34 publications
19
584
0
34
Order By: Relevance
“…58 Mouse NAIP is mainly expressed in macrophages and is encoded by seven paralogous genes, naip1 to naip7. 60 NAIP was proposed to interact with IPAF indicating that it may be part of the same caspase-1 activating complex 61 (Figure 2). NALPs, represent the largest NLRs subfamily 57 (Table 1).…”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
See 1 more Smart Citation
“…58 Mouse NAIP is mainly expressed in macrophages and is encoded by seven paralogous genes, naip1 to naip7. 60 NAIP was proposed to interact with IPAF indicating that it may be part of the same caspase-1 activating complex 61 (Figure 2). NALPs, represent the largest NLRs subfamily 57 (Table 1).…”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
“…100,101 Similarly, other studies showed that NAIP5, a mouse parologue of NAIP, possibly in combination with IPAF, recognizes intracellular flagellin from Legionella pneumophila, in order to induce caspase-1 activation. 61,102,103 Moreover, early genetic studies in mice clearly identified NAIP5 as a L. pneumophila susceptibility locus, further delineating the importance of inflammatory caspases in the control of bacterial pathogens. 104 NALPs and the Biology of Reproduction: A Role for the Inflammatory Caspases?…”
Section: Intracellular Flagellin: Detection By the Nlr Proteins Naip mentioning
confidence: 99%
“…Several bacterial strains possess delivery systems responsible for the translocation of effector molecules into the host cytosol, which permit bacterial internalization and/or replication. 87,88 Disruption of the type four secretion system in Legionella pneumophila, 53,54,89 of the Listeria monocytogenes listeriolysin O, or of the type three secretion system in Salmonella typhimurium, 47,82,83 Shigella flexneri, 90 Yersinia pseudotuberculosis 55 and Pseudomonas aeruginosa 51 inhibits caspase-1 activation by these pathogens. Although initial reports had proposed that proteins of the type three secretion system, SipB in Salmonella 44 and IpaB in Shigella, 43 could directly bind and activate caspase-1, recent studies indicate a more indirect role for such bacterial delivery systems, presumably by allowing the inflammasome agonist to reach the cytosol.…”
Section: Modulation Of Caspase-1 Activitymentioning
confidence: 99%
“…23,24 There is some evidence that that NAIP can assemble with IPAF to form heterocomplex inflammasomes. 25,26 NLRP1 can also associate with NOD2 to mediate caspase-1-dependent IL-1b secretion in response to Bacillus anthracis and MDP. 27,28 Recently a fourth type of inflammasome has been identified, involving the protein absent in melanoma 2 (AIM2) (Figure 1).…”
Section: The Inflammasomesmentioning
confidence: 99%